The sweetest sound - Winston, Sherri (Little, Brown and Company, 2017)
"Shy ten-year-old Cadence grapples with an overprotective father, a mother who's skipped town to pursue stardom, and what to do when a recording of her amazing voice leaks before she's ready to share it with the world"--